Emergy evaluation of a swamp dike-pond complex: A new ecological restoration mode of coal-mining subsidence areas in China. (December 2019) - Sun, Jinfang; Yuan, Xingzhong; Liu, Hong; Liu, Guodong; Zhang, Guanxiong
Highlights: Ecological restoration modes were studied by performing emergy analysis. The environmental loading ratio for the ecological restoration system was 0.39. The sustainability index value for ecological restoration system was high. Ecological restoration system shows superior ecological functions and services. Abstract: The swamp dike-pond complex (SDPC) is a mode of ecological restoration in coal-mining subsidence areas in China that consists of an engineered swamp and an engineered dike-pond. The aim of this study is to compare conventional reclamation and ecological restoration systems by performing emergy analysis. The analysed systems included an SDPC and contrasting fish ponds (CFP) in a stabilized subsidence area and an SDPC in a submergence area that can be used as a transition system during the course of the succession of coal-mining subsidence areas. Indices, ratios and ternary diagrams based on emergy can be used to assess the behaviours of the three systems. Emergy analysis was well suited for this task because it was capable of converting all energies, materials and information to a common unit of quality to allow for deep comparisons across the three systems. The results show that the SDPC was most dependent upon renewable resources, and efforts were made to maintain the natural mechanisms of energy and matter flow regulation as much as possible. Therefore, the SDPC has greater emergy efficiency in terms of biological energy use and the level of environmental loading. The CFP was more dependent on the fraction of purchased inputs and nonrenewable inputs from the outside. The sustainability index values for the three systems ranged from 0.82 for the CFP in the stabilized subsidence area to 4.31 for the SDPC in the submergence area and 9.12 for the SDPC in the stabilized subsidence area. The results confirm that the SDPC is less stressful on the environment and more sustainable than the CFP in coal-mining subsidence areas. In addition, the respective ecosystem service values for each system were 1.52E + 17 sej/yr/ha for the SDPC in the stabilized subsidence area and 2.90E + 16 sej/yr/ha for the SDPC in the submergence area, which were 10.1 and 1.9 times higher than the value for the CFP, respectively. This research suggests that vegetation, faunal communities and functional hydrology, which support the entire ecosystem via the food web, can be restored in the SDPC, and restored wetlands can provide economic and ecological benefits via the return of their ecological services and functions. Endangered and rare species, such as Baer's pochard ( Aythya baeri ) and reed parrotbill ( Paradoxornis heudei ), were found in this area, and the prospects of such species depend on future restoration policies in coal-mining subsidence areas in China. To safeguard biodiversity, SDPCs should be preferred over other reclamation methods. This work will inform environmental policy making and be used to recommend better management practices to the government.